Finding me [large type] - Davis, Viola, 1965- (Ebony Magazine Publishing, Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
"In my book, you will meet a little girl named Viola who ran from her past until she made a life-changing decision to stop running forever. This is my story, from a crumbling apartment in Central Falls, Rhode Island, to the stage in New York City, and beyond. This is the path I took to finding my purpose but also my voice in a world that didn't always see me. As I wrote [this book], my eyes were open to the truth of how our stories are often not given close examination. We are forced to reinvent them to fit into a crazy, competitive, judgmental world. So I wrote this for anyone running through life untethered, desperate and clawing their way through murky memories, trying to get some form of self-love. For anyone who needs reminding that a life worth living can only be born from radical honesty and the courage to shed facades and be ... you"--Back cover